Bonifacio's bolo - Ocampo, Ambeth R., 1961- (Pasig City : Anvil Pub, 1995)
Most article were from the author's column in the Philippines Daily Inquirer published from 1992-1993
Keywords: Philippines -- History -- Annecdotes; Philippines -- History -- Errors, inventions, etc